Modulatory Effects of Huoxiang Zhengqi Oral Liquid on Gut Microbiome Homeostasis Based on Healthy Adults and Antibiotic-Induced Gut Microbial Dysbiosis Mice Model - Min Gao; Xinhao Duan; Xiang-Ru Liu; Shiyue Luo; Shixin Tang; Hao Nie; Jing Yan; Zhen Zou; Zhen Zou; Chengzhi Chen; Chengzhi Chen; Qi Yin; et al. (Frontiers Media S.A., 2022)
Traditional herbal medicine (THM) is used worldwide for its safety and effectiveness against various diseases. Huoxiang Zhengqi (HXZQ) is an extensively used Chinese THM formula targeting gastrointestinal disordered gastroenteritis via regulating the intestinal microbiome/immuno-microenvironment. However, the specific mechanisms remain largely unexplored, besides as a lifestyle drug, its safety on the gut microbiome homeostasis has never been investigated. In this study, the effects of HXZQ on the gut microbiome of healthy adults were investigated for the first time, and the antibiotic-induced gut microbiota dysbiosis mice model was applied for verification. Based on healthy adults, our results revealed that HXZQ exhibited mild and positive impacts on the bacterial diversity and the composition of the gut microbiome in a healthy state. As for an unhealthy state of the gut microbiome (with low bacterial diversity and deficient compositions), HXZQ significantly restored the bacterial diversity and recovered the abundance of Bacteroidetes. In the antibiotic-induced mice model, HXZQ distinctly revived the deficient gut microbial compositions impaired by antibiotics. At the genus level, the abundances that responded most strongly and positively to HXZQ were Bifidobacterium in healthy adults and Muribaculaceae, Lactobacillus, and Akkermansia in mice. In contrast, the abundance of Blautia in healthy adults, Enterococcus, and Klebsiella in mice showed inversely associated with HXZQ administration. At last, HXZQ might exhibit an anti-inflammatory effect by regulating the concentration of interleukin-6 in plasma while causing no significant changes in the colon tissue structure in mice. In conclusion, our results elucidate that the safety of HXZQ in daily use further reveals the modulatory effects of HXZQ on gut microbial community structure. These results will provide new insights into the interaction of THM and gut microbiome homeostasis and clues about the safe use of THM as a lifestyle drug for its further development.